Civil Religion di Indonesia - Parmudi, Mochamad (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2018)
Indonesia is a democracy. Therefore the government must encourage and guarantee freedom of speech, religion, opinion, an association for every citizen. The government must enforce the rule of law which the majority must respect the rights of minority groups and their citizens give each other equal opportunities to live together to get a decent life. The Republic of Indonesia is a unitary state with a high degree of plurality in the fields of religion, ethnicity, race, and class. To support religious life, the national and state community in a peaceful, healthy, prosperous and happy manner, civil religion is needed. This research is a phenomenological study focusing on analyzing the description and explanation of civil religion in Indonesia. A phenomenological approach is used in interpreting the